Glanzmann's Thrombasthenia: How Listening to the Patient Is Sometimes the Simple Key to Good Medicine!. (10th July 2020) - Jayakrishnan, Thejus T.; Limonnik, Vladimir; Shah, Deep; Mewawalla, Prerna
Abstract : Introduction . Glanzmann's thrombasthenia is a rare clotting disorder caused by impaired platelet function. Lack of awareness of the appropriate management of rare medical conditions may lead to patient dissatisfaction and potentially poor treatment outcome. Case Report . A 78-year-old male with a history of Glanzmann's thrombasthenia was admitted to the trauma service following a fall in which he sustained a facial laceration as well as maxillary sinus and nasal fractures. He received DDAVP 20 mcg and tranexamic acid upon presentation to the emergency department (ED). In the ED, the patient requested administration of platelet transfusion but was refused due to a normal platelet count. During the course of his hospital stay, he complained of epistaxis and was noted to have a downtrending hemoglobin from 11.0 g/dl to 9.0 g/dl. The patient and his family were not comfortable when the discharge plan was finalized and demanded platelet transfusion (due to history of needing platelets in association with injuries or procedures in the past) was refused by the primary team as they continued to state that his platelet count is normal. On hospital day 3, hematology was consulted as the patient and his family were extremely angry and hematology recommended platelet transfusion. Further clinical information was not available as the patient was transferred to another facility per family request as they wanted to be at a center which had the patient's primary hematologist. Discussion . A delay in specialist consultation resulted in patient dissatisfaction and extended the length of stay. Patients with rare medical conditions and potential for major complications should be managed aggressively with appropriate specialist consultation to promote patient satisfaction and improve the overall quality of care. This case shows that as physicians it our duty to listen to our patient's concerns and involve them in the medical decision-making to provide optimal patient-centered care.